2003
DOI: 10.1063/1.1566791
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up approach for carbon nanotube interconnects

Abstract: We report a bottom-up approach to integrate multiwalled carbon nanotubes (MWNTs) into multilevel interconnects in silicon integrated-circuit manufacturing. MWNTs are grown vertically from patterned catalyst spots using plasma-enhanced chemical vapor deposition. We demonstrate the capability to grow aligned structures ranging from a single tube to forest-like arrays at desired locations. SiO2 is deposited to encapsulate each nanotube and the substrate, followed by a mechanical polishing process for planarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
262
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(276 citation statements)
references
References 17 publications
4
262
0
Order By: Relevance
“…1,2 The suppression of carrier backscattering brought about by the nanotube's band structure results in long mean free paths leading to ballistic transport and opens up the possibility of GHz and sub-THz applications. 3 Tailoring the intrinsic electronic properties of the CNT by choosing semiconducting or metallic CNTs has already led to the fabrication of field effect transistors 3 and sensors 4 for the former type of nanotube and interconnects 5 and field emission materials 6 for the latter.…”
mentioning
confidence: 99%
“…1,2 The suppression of carrier backscattering brought about by the nanotube's band structure results in long mean free paths leading to ballistic transport and opens up the possibility of GHz and sub-THz applications. 3 Tailoring the intrinsic electronic properties of the CNT by choosing semiconducting or metallic CNTs has already led to the fabrication of field effect transistors 3 and sensors 4 for the former type of nanotube and interconnects 5 and field emission materials 6 for the latter.…”
mentioning
confidence: 99%
“…111 The possible application of VANTAs and VACNFs as microelectronic interconnects has driven many studies to characterize their end-contact quality. 71,[111][112][113][114][115] The reported end-contact resistances vary significantly from one measurement to another suggesting a wide spectrum of influencing parameters. Important parameters are the surface roughness of the metal underlayer as well as its surface oxidation, 115 the wettability of the metal underlayer and its work function, 112 and the growth conditions.…”
Section: Quality Factormentioning
confidence: 99%
“…Zhang et al 69 as well as other groups [70][71][72] have investigated the current-voltage (I-V) characteristic of individual VACNFs using accurate four-point probe measurements and showed that they exhibit linear behavior. They observed an average VACNF resistivity of 4.23 Â 10 À3 XÁcm which is consistent with a simple model of charge transport where electrons travel mainly from one graphitic plane to another along the length of the nanofiber.…”
Section: Modelingmentioning
confidence: 99%
“…CNT exhibit impressive potentials in many applications such as electrical interconnects, (Kreupl et al 2004;Li et al 2003) thermal interface materials, (Biercuk et al 2002;Liu et al 2004) high-performance fibers, (Koziol et al 2007;Vigolo et al 2000), environmental monitoring (Lee, Sun, and Ling 2009;Lee et al 2010), and health & biotechnology (Ghule et al 2007) so on. Although the theoretical intrinsic electrical, thermal, and mechanical properties of an individual CNT are extraordinary, synthesized CNTs in reality are far from being defectfree.…”
Section: Carbon Nanotube and Microwave Interactionmentioning
confidence: 99%